Prevalence of various dermatoses in pregnancy at a tertiary care centre in Moradabad, Uttar Pradesh, India: an observational study - Uniyal, Shruti; Agarwal, Ritika; Nandi, Nupur; Jain, Pulkit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This was a prospective study which was done to observe various skin lesions in pregnancy and to determine the most likely causes and their incidence in antenatal patients, it was noticed that many women in our institute were having pregnancy related cutaneous complaints thus this observational study was carried out so that better preventive measures and treatment options could be provided to these patients. Methods: Study was conducted in out-patient department of Obstetrics and Gynaecology, TMU, Moradabad. All ANC cases between October 2017 to September 2018 having any type of dermatoses were included in the study irrespective of gestational age. 6348 patients appeared in OPD in the given time period out of which 1256 were included. In case of pruritus, liver function tests were done with USG whole abdomen and patients were reviewed by physician if required. Screening with VDRL, HCV, HbSAg and ELISA for HIV was done in all. Results were tabulated and analyzed. Results: 50.8% primi gravidas ,49.2% multi gravidas. age range 18-38 years. 29.3% presented in third trimester ,25.6% presented in second trimester. Physiological changes seen in all cases, 8.68% specific dermatoses of pregnancy. 40.4 % no complaints, 5.65% melasma, 90.8% hyperpigmentation, 94.6% linea nigra. Secondary areola 89.3%,striae 80.3% out of which 38.9%- primi gravidas and 41.40% -multi gravidas. 92.9% no change in hair density. Montgomery’s tubercles 30-50% of cases. spiders nevi 67%. No cases of palmar erythema. Pruritus gravidarum 38.53%. PUPPP 28.4%. Pemphigoid Gestationis 9.17%. Prurigo of pregnancy 18.34%. Pruritic folliculitis 1.8%. Eczema in pregnancy : pre-existing in 3.7% , out of which exacerbation 1, 3 unaffected. 3 chicken pox.1 filariasis.24 herpetic lesions (herpes simplex).1 scleroderma.17.27% pre-existing taenia infection . Scabies 20.46%.11 0.87% dual infection (scabies-taenia). Conclusions: This study highlights high prevalence of community acquired infections in our region like taenia, scabies giving rise to skin lesions in Antenatal women. Moreover, it highlights a probable association between the prevalence of skin lesions with factors like poor personal hygiene, overcrowding, low socioeconomic status, anaemia and poor nutritional status.